Spiritual care in nursing: a concept analysis. (9th April 2014) - Ramezani, M.; Ahmadi, F.; Mohammadi, E.; Kazemnejad, A.
<x xml:space="preserve">Abstract</x> Background Around the world, spiritual care in nursing is a critical part of providing holistic care, but within our profession, there is a lack of certainty over the meaning of spirituality and delivery of spiritual care, including nurses thinking of spirituality as religion. Methods We adopted the eight‐step Walker and Avant's concept analysis approach to provide a definition of the concept, searching and analysing international and national online databases. Inclusion criterion included that articles were published between 1950 and 2012 in English or Persian language. Finally, 151 articles and 7 books were included in the analysis. Findings The attributes of spiritual care are healing presence, therapeutic use of self, intuitive sense, exploration of the spiritual perspective, patient‐centredness, meaning‐centred therapeutic intervention and creation of a spiritually nurturing environment. Spiritual care is a subjective and dynamic concept, a unique aspect of care that integrates all the other aspects. It emerges in the context of nurses' awareness of the transcendent dimension of life and reflects a patient's reality. The provision of spiritual care leads to positive consequences such as healing for patients and promotion of spiritual awareness for nurses. Implications for Nursing and Health Policy The conceptual definition of spiritual care provided in this study can help clinical nurses, educators and nurse managers to develop and implement evidence‐based health policies, comprehensive staff training programmes and practical quality assessment guidelines to try to ensure that all nurses are competent to include relevant spiritual care in practice. Conclusion A comprehensive definition of the concept of spiritual care ensued. The findings can facilitate further development of nursing knowledge and practice in spiritual care and facilitate correction of common misconceptions about the provision of spiritual care.